PENGEMBANGAN ṢHADAQĀH SEBAGAI SEBUAH KONSEP PEMBERANTASAN PRAKTIK RIBAWI: Studi di Kota Banda Aceh dan Aceh Besar - Amri, Aulil; Naylul Muna, Suci (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2022)
The practice of usury that occurs among the community can have a negative impact onthe economy, cause injustice and create social in society. This has also been warned in the AlQuran Surah Al-Baqarah verse 276 where Allah SWT guarantees a solution for the eradication ofthe practice of usury because to deal with usury, planned stages and strategies are also neededand the main strategy to eradicate it is to activate ṣhadaqāh. Therefore, the author is interested inexamining how hadaqāh can have an impact on eradicating usury practices that occur in societyor how the implementation of ṣhadaqāh as an instrument for eradicating usury because nowadaysthere are many practices of usury, especially in the markets. In this study, the authors used aqualitative approach and for analysis the authors used descriptive analysis. In obtaining the data,the author uses the method of interview, observation and documentation. The results of this studyare proving that hadaqah has an impact on reducing the practice of usury that occurs in societybecause usury does not occur in obtaining welfare, usury does not meet the requirements as asource of legal ownership in Islam. Therefore, having ṣhadaqāh funds which are then managedand used as interest-free loans provided by the Baitul Misykat to traders in the market really helpsthem in terms of business capital so that they no longer need to make credit to moneylenders orother loans that contain usury elements. . Thus the practice of usury that occurs in the market isreduced. Actions based on the results of usury become unworthy or unblessed, while ṣhadaqāhcan be seen as a stable or consistent instrument in the circulation of wealth that aims to buildwelfare. Ṣhadaqāh can maintain a business balance that is free from the usury system.